Transcriptional regulation in the absence of inositol trisphosphate receptor calcium signaling - Young, Michael; Booth, David M.; Smith, David; Tigano, Marco; Hajnόczky, Gyӧrgy; Joseph, Suresh K. (Frontiers in Cell and Developmental Biology, 2024)
The activation of IP3 receptor (IP3R) Ca2+ channels generates agonist-mediated Ca2+ signals that are critical for the regulation of a wide range of biological processes. It is therefore surprising that CRISPR induced loss of all three IP3R isoforms (TKO) in HEK293 and HeLa cell lines yields cells that can survive, grow and divide, albeit more slowly than wild-type cells. In an effort to understand the adaptive mechanisms involved, we have examined the activity of key Ca2+ dependent transcription factors (NFAT, CREB and AP-1) and signaling pathways using luciferase-reporter assays, phosphoprotein immunoblots and whole genome transcriptomic studies. In addition, the diacylglycerol arm of the signaling pathway was investigated with protein kinase C (PKC) inhibitors and siRNA knockdown. The data showed that agonist-mediated NFAT activation was lost but CREB activation was maintained in IP3R TKO cells. Under base-line conditions transcriptome analysis indicated the differential expression of 828 and 311 genes in IP3R TKO HEK293 or HeLa cells, respectively, with only 18 genes being in common. Three main adaptations in TKO cells were identified in this study: 1) increased basal activity of NFAT, CREB and AP-1; 2) an increased reliance on Ca2+- insensitive PKC isoforms; and 3) increased production of reactive oxygen species and upregulation of antioxidant defense enzymes. We suggest that whereas wild-type cells rely on a Ca2+ and DAG signal to respond to stimuli, the TKO cells utilize the adaptations to allow key signaling pathways (e.g., PKC, Ras/MAPK, CREB) to transition to the activated state using a DAG signal alone.